On the memory of products of long range dependent time series - Christian Leschinski (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2016)
This paper derives the memory of the product series xtyt, where xt and yt are stationary long memory time series of orders dx and dy, respectively. Special attention is paid to the case of squared series and products of series driven by a common stochastic factor. It is found that the memory of products of series with non-zero means is determined by the maximal memory of the factor series, whereas the memory is reduced if the series are mean zero.
Keywords: C22; C10; 330; Long Memory; Products of Time Series; Squared Time Series; Fractional Cointegration